2014
DOI: 10.1590/s0104-66322014000100005
|View full text |Cite
|
Sign up to set email alerts
|

On the prediction of pickup and saltation velocities in pneumatic conveying

Abstract: -This paper presents a comparative study of the critical pickup and saltation velocities of particles in horizontal pipelines for pneumatic conveying design. A comparative study is performed using different existing correlations in the literature for the determination of the minimum velocity of transport as a function of the particle and pipe diameter, particle density, solid mass flow rate and particle sphericity. Their limitations and difficulties in predicting those critical velocities are analyzed. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Experimental results here reveal a surprising nonmonotonic relationship between U pu and PSD width, which deviates from what is expected from the results of binary mixtures (Goy et al, 2011). As for (b), some researchers have shown experimentally that non-spherical (Geldart Groups A and C) particles in general have a greater U pu than spherical particles (Hayden et al, 2003), and nonspherical, coarse (Geldart Group D) particles exhibit a lower characteristic Ar (Kalman et al, 2005), while others taken an analytical approach and developed a complex empirical correlation whose utility is limited beyond the systems investigated (Gomes and Mesquita, 2014;Kalman et al, 2005). The new contributions of this work with regards to particle sphericity are in (i) providing plausible hypotheses for a more mechanistic understanding of the impact of sphericity, and (ii) presenting results on the combined effects of sphericity and continuous PSDs.…”
Section: Introductionmentioning
confidence: 79%
“…Experimental results here reveal a surprising nonmonotonic relationship between U pu and PSD width, which deviates from what is expected from the results of binary mixtures (Goy et al, 2011). As for (b), some researchers have shown experimentally that non-spherical (Geldart Groups A and C) particles in general have a greater U pu than spherical particles (Hayden et al, 2003), and nonspherical, coarse (Geldart Group D) particles exhibit a lower characteristic Ar (Kalman et al, 2005), while others taken an analytical approach and developed a complex empirical correlation whose utility is limited beyond the systems investigated (Gomes and Mesquita, 2014;Kalman et al, 2005). The new contributions of this work with regards to particle sphericity are in (i) providing plausible hypotheses for a more mechanistic understanding of the impact of sphericity, and (ii) presenting results on the combined effects of sphericity and continuous PSDs.…”
Section: Introductionmentioning
confidence: 79%
“…Then, Goy et al 13 determined mixed Geldart's particle pickup velocities by the mass loss method and determined that the empirical equations have limitations for zone I and zone II binary mixed-particle pickup velocity calculations. Then, Gomes and Mesquita 14 conducted a similar study and focused on the influence of particle shape and particle size on the pickup velocity. Next, Soepyan et al 15 developed a semi-mechanistic equation and quantified its determinacy by the bootstrap method.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, if the transport velocity is kept minimum based on knowledge of Upu, particle breakage can be reduced considerably in dilute phase transport systems (Kalman, 2000;Salman et al, 2002). Despite the advances on Upu to date, Gomes and Mesquita (2014) very recently compared various Upu correlations and detected discrepancies of about an order-of-magnitude in Upu predictions and contradictory shapes (convex/ concave) for the Upu versus particle diameter (dp) trends, which signals the need for improved mechanistic understanding. Although in practice particle systems are typically polydisperse, much of the earlier work has focused on monodisperse systems or only reported dp ranges without specifying polydispersity.…”
Section: Horizontal Pneumatic Conveyingmentioning
confidence: 99%
“…The same authors Gomes and Mesquita (2014) also recently reviewed all available Upu correlations and found that their model predictions were contradictory.…”
Section: Fig 22mentioning
confidence: 99%